Strengthening Village Economy through Village-Owned Business Agencies in Sharia Maqasid - Muhammad Alwi Sihab Bashari (Maliki Islamic Economics Journal, 2021)
BUMDES in recent years has indeed become the subject of conversation, not only by ordinary people but also among researchers and students. This is understandable, because the existence of BUMDES has a strategic role in the midst of society, especially in rural areas. If examined carefully the nature of BUMDES is not merely as a commercial economic institution, but also as a means to improve community welfare, in this study aims to describe the BUMDES Gesang business units. Analyzing the role of BUMDES in strengthening the village economy in the village of Gesang, Tempeh sub-district, Lumajang Regency, which was then reviewed from the perspective of the Islamic maqasid. The research method used in this study is a qualitative research type of research is field research which in data collection using interviews, observation and documentation. While for data analysis techniques, namely by reducing the data presentation of data and drawing conclusions while for checking the validity of the data is to use triangulation. The results of this study can be seen that: Gesang BUMDES business units there are three agricultural units, service units and HIPPA units.